Neural processing of emotion in multimodal settings - Klaus Mathiak (Frontiers Research Topics, 2015)
Our everyday life is characterized by a multitude of emotionally relevant cues that we perceive and communicate via various sensory channels. This does not only encompass the obvious cases of auditory and visual modalities, but also olfactory, gustatory, and even tactile stimuli. Any kind of emotional situation in a natural setting is usually a multimodal experience: A friend welcomes us with warm words, a smile, and a happy voice; the sight of our favourite food is accompanied by a seductive smell and a delicious taste; the thrill of watching an exciting movie scene is intensified by a gripping soundtrack. In these situations, the signals from various senses do not stand on their own; they interact and create a unified emotional experience. Recent neuroscientific research has begun to accommodate this inherent multimodality of emotions in natural situations by studying the interaction of affectively relevant information from more than one sensory channel. Fascinating new aspects emerge concerning the neurobiology of emotion processing, and there is evidence that integrating emotional cues from various sources invokes brain processes that go beyond the well-known patterns observed during unimodal stimulation. The aim of this volume is to present novel and interesting studies dealing with the multimodality of emotions and their neural processing. This includes findings from novel paradigms beyond the classical stimulus-response pattern, fascinating new insights into the interaction of the chemical senses, new analysis methods, comprehensive reviews of selected topics, multimodality in social interactions, and clinical perspectives. Taken together, the studies of this volume thus help us to better understand the interplay of various senses in our daily emotional experiences.